Pd nanoparticles decorating flower-like Co3O4 nanowire clusters to form an efficient, carbon/binder-free cathode for Li–O2 batteries1. Issue 30 (14th August 2015) - Leng, Limin; Zeng, Xiaoyuan; Song, Huiyu; Shu, Ting; Wang, Haishui; Liao, Shijun
<x xml:space="preserve">Abstract</x> A novel high-performance flower-like Co3O4 nanowire cluster decorated with Pd nanoparticles to form a carbon/binder-free cathode for Li–O2 batteries.